Human Resource Management Competency Strategies in Enhancing the Competitiveness of Micro Businesses - Danung Kuswantoro Putro; Suhartini (Cita konsultindo, 2026)
Human resource management competency refers to the abilities, knowledge, and skills of individuals or groups in managing the strategic and operational aspects of an organization's workforce. This study aims to answer the question of how PT Beranda Sadawira Utama's human resource competency strategy has improved the competitiveness of micro businesses. This study uses a descriptive qualitative method with purposive techniques and data collection in the form of interviews, observations, and documentation. The results show that PT Beranda Sadawira Utama has implemented the KSA concept and produced a VRIN value, proving that the company uses strategies such as implementing product quality standards, communication regarding services, and consistent cooperation with colleagues, which have resulted in the company's ability to survive and increase its business competitiveness.